Personalized Genetic Testing and Norovirus Susceptibility. Issue 4 (2014) - Prystajecky, Natalie; Brinkman, Fiona SL; Auk, Brian; Isaac-Renton, Judith L; Tang, Patrick
Abstract : BACKGROUND: The availability of direct-to-consumer personalized genetic testing has enabled the public to access and interpret their own genetic information. Various genetic traits can be determined including resistance to norovirus through a nonsense mutation (G428A) in the FUT2 gene. Although this trait is believed to confer resistance to the most dominant norovirus genotype (GII.4), the spectrum of resistance to other norovirus strains is unknown. The present report describes a cluster of symptomatic norovirus GI.6 infection in a family identified to have norovirus resistance through personalized genetic testing. CASE PRESENTATION: In January 2013, four members of a family determined by a direct-to-consumer genetic test to be homozygous for the norovirus resistance trait (A/A genotype for single nucleotide polymorphism rs601338) developed symptoms consistent with acute viral gastroenteritis. Stool and vomitus samples were submitted for enteric viral pathogen testing. Samples were positive for norovirus GI.6 in three of the four cases. CONCLUSIONS: The present report is the first to describe norovirus GI.6 infection in patients with the G428A nonsense mutation in FUT2 ; this cluster of cases suggests that the G428A mutation in FUT2 may not confer resistance to norovirus GI.6. Direct-to-consumer genetic testing is empowering members of the public to identify novel associations with their genetic traits. Expert consultation is important for the interpretation of personalized genetic test results, and follow-up laboratory testing can confirm any potentially novel associations.